2018
DOI: 10.4314/njt.v37i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties of crosslinked natural rubber composites reinforced with cellulosic nanoparticles

Abstract: The dynamic mechanical analysis (DMA) of crosslinked natural rubber nanocomposites reinforced with cellulosic nanoparticles obtained from lignocelluloses biomass (coconut husk, bamboo culm and cotton linters) has been investigated and compared with carbon black filled natural rubber vulcanizate. The crosslinked natural rubber matrix based composites were produced by melt intercalation process using two roll mixing mill and vulcanized in a thermally regulated hydraulic press. DMA were carried out in order to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Loss modulus defines the heat energy lost per cycle of deformation [18]. It also provides information on the viscous nature of materials.…”
Section: Discussionmentioning
confidence: 99%
“…Loss modulus defines the heat energy lost per cycle of deformation [18]. It also provides information on the viscous nature of materials.…”
Section: Discussionmentioning
confidence: 99%
“…The control showed a higher water absorption compared to the WF0/CB60 due to the absence of carbon black and fibers in its composition. In this case, carbon black reduces the empty spaces left by the rubber at the time of its vulcanization, that is, the presence of carbon black in the WF0/CB60 treatment contributed to the reduction of water absorption by the sample [19] .…”
Section: Water Absorptionmentioning
confidence: 99%
“…However, whereas the increase in loss modulus as temperature increases can be easily seen in the curves of these works, the curves of this research may not be seen; this is because of the temperature range of the experiment. Oboh et al reported that the best way to interpret these curves is to view them as force versus energy dissipation rather than modulus versus temperature, thus upon initial heating, though the material will be less stiff, more force will be dissipated as heat, increasing the loss modulus; as the temperature continues to increase above a critical point as a result of further heating, there will be a reduction in molecular friction and hence less energy will be dissipated leading to a decrease in loss modulus [12].…”
Section: Loss Modulusmentioning
confidence: 99%
“…The studies of physical properties of composites such as density and water absorption characteristics by researchers are prompted by the quest to get engineering materials that have less weight for use in industries like airspace and automobile and to check the reliability of these materials in humid environments. Dynamic mechanical analysis is used to indicate the molecular relaxation dynamics of material [12]. The objective of this study is to evaluate the density, water absorption characteristics and dynamic mechanical analysis of polyester when reinforced with varying quantities of coconut husk ash.…”
Section: Introductionmentioning
confidence: 99%